Intravitreal injections of corticosteroid and the risk of central serous chorioretinopathy - Jae Ryong Song; Se Joon Woo (PLoS ONE, 2026)
Central serous chorioretinopathy (CSC) is strongly associated with systemic corticosteroid use, but the risk following intravitreal steroid injections remains unclear, with limited evidence from isolated case reports. This study evaluated the association between intravitreal steroid injections and CSC development using a dual-approach design with Clinical Data Warehouse (CDW) analysis and choroidal thickness validation. We performed CDW analysis of 2,336 patients receiving intravitreal triamcinolone acetonide or dexamethasone implant over 21 years (April 2003–October 2024), screening for CSC within 6 months post-injection. Additionally, we conducted detailed subfoveal choroidal thickness analysis in 269 eyes (January 2023–October 2024) at baseline, 1, 3, and 6 months post-injection using optical coherence tomography. No confirmed CSC cases occurred in either cohort (0/2,336 patients, 95% CI: 0–0.13%; 0/269 eyes). Contrary to the choroidal thickening characteristic of CSC, both steroid formulations produced significant choroidal thinning at 1 month: dexamethasone implant (227.0 ± 65.4μm to 217.9 ± 62.0μm, p < 0.0001) and triamcinolone acetonide (219.8 ± 78.7μm to 218.6 ± 77.7μm, p < 0.0001). Only 4.9% of eyes showed ≥10% choroidal thickening, and none developed CSC features. Both formulations achieved significant macular edema reduction through 6 months. Intravitreal corticosteroids showed no confirmed CSC cases over two decades with choroidal thinning rather than the thickening characteristic of CSC, suggesting distinct pathophysiological mechanisms and a favorable safety profile regarding CSC development.